Trading on long-term information - Corey Garriott; Ryan Riordan (Bank of Canada, 2020)
Predatory trading discourages informed investors from gathering information and trading on it. However, using 11 years of equity trading data, we do not find evidence that informed investors are being discouraged. They have roughly constant volumes and profits through the sample. They are sophisticated, trading patiently over weeks and timing their trading to achieve negative price impacts, leaving price efficiency unchanged. We identify shorter-term traders and, in contrast to theory, find that they supply liquidity by trading in the opposite direction of the informed. Inefficient prices may be the result of informed investors' sophisticated trading and not of predatory short-term trading.
Keywords: G20; G14; L1; 330; Financial markets; Market structure and pricing; Financial institutions